Implementasi Nilai-Nilai Pancasila Presiden Joko Widodo Sebagai Cara Meminimalisir Korupsi Di Negara Demokrasi - Fadiyah, Dina (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2023)
This article will discuss the implementation of President Joko Widodo's Pancasila values as a way to minimize corruption in democratic countries. Indonesia, as one of the democratic and developing countries that has a fairly high level of corruption in the world, is a fact that we still need to do a lot so that this title can fade from Indonesia's mind. One way is to instill Pancasila values in all Indonesian society without exception. This research uses implementation theory combined with descriptive qualitative research methods with literature review and literature study data collection techniques, it is hoped that it will be a contribution to social science today. The result is that President Joko Widodo has succeeded in implementing Pancasila values in Indonesia, this argument is proven by various policies and reforms related to Pancasila carried out in the current era.